2021
DOI: 10.3389/fvets.2021.658301
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of In Ovo Injection of Synbiotics on the Early Growth Performance and Intestinal Health of Chicks

Abstract: In this study, the effects of synbiotic inclusion at the intra-amniotic stage in layer chicks were evaluated with different parameters, such as performance, immunological function, intestinal development, and cecal microflora content. A total of 1,200 eggs with fertile embryos were allocated into four treatment groups. For every treatment, five replicates were used, and 60 eggs were included in each replicate. The following four treatment groups were established: the non-injected group, 0.9% physiological sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 44 publications
3
21
0
Order By: Relevance
“…Besides, our investigation also indicated that 400 mg/kg LP stimulated the development of immune organs such as thymus and bursa of fabricius of Pekin ducks . Similarly, previous studies have shown that LP slightly increases thymus index in egg-laying chickens infected with Clostridium perfringens ( Xu et al., 2020 ), and enhances thymus and bursa of fabricius indices of chicks ( Duan et al., 2021 ). The ameliorated growth performance and organ indices of ducks in the present study may have relation with the beneficial changes in immunity, TJ proteins, and microbiota, which are categorized as intestinal health.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Besides, our investigation also indicated that 400 mg/kg LP stimulated the development of immune organs such as thymus and bursa of fabricius of Pekin ducks . Similarly, previous studies have shown that LP slightly increases thymus index in egg-laying chickens infected with Clostridium perfringens ( Xu et al., 2020 ), and enhances thymus and bursa of fabricius indices of chicks ( Duan et al., 2021 ). The ameliorated growth performance and organ indices of ducks in the present study may have relation with the beneficial changes in immunity, TJ proteins, and microbiota, which are categorized as intestinal health.…”
Section: Discussionsupporting
confidence: 62%
“…Gut microbes play an integral role in host feed utilization efficiency and maintenance of the intestinal homeostasis ( Pan and Yu, 2014 ). Dietary LP could modulate the abundance of beneficial bacteria and potential pathogens in the gut of broilers ( Shen et al., 2014 ; Wu et al., 2018 ; Duan et al., 2021 ). Our results revealed that supplementation of 400, 800 mg/kg LP increased the relative abundance of Firmicutes and decreased Bacteroidetes , which have a positive effect in facilitating growth performance and negative impact in serum proinflammatory factor IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…Some synbiotics, such as raffinose with Lactococcus lactis ssp. cremoris IBB SC1, lactose with Lactobacillus acidophilus and Streptococcus faecium ( 142 ), and Lactobacillus plantarum with Astragalus polysaccharide, or probiotics, such as Lactobacillus plantarum with an increased feed conversion ratio ( 143 ). These conflicting results are likely due to the types of bioactive substances, dosages, environmental conditions, and management differences.…”
Section: Birds' Performancementioning
confidence: 99%
“…Duan et al ( 122 ) studied the effect of IOF of L. plantarum and astragalus polysaccharide at ED 18.5. The IOF of this synbiotic improved the growth performance, immunity, and morphology of the small intestine and cecal microflora.…”
Section: In Ovo Delivered Bioactive Compounds and Their Effectsmentioning
confidence: 99%